Brand Velocity Partners - Rosenthal, Jean W., 1945-; Baron, James N.; Choi, James J.; Elias, Jaan (London : Yale School of Management, 2021)
When Steve Lebowitz and Drew Sheinman first met, they found they both believed that the private equity (PE) model of investing was ripe for disruption. They observed that PE firms were dominated by finance professionals, yet many of the PE-owned companies needed more than financial engineering. In 2019, Lebowitz and Sheinman, along with Austin Ramos and Larry Rothstein, formed Brand Velocity Partners ("BVP"). The partners rallied around the notion that brand building, along with traditional financial expertise, could unlock immense value across a wide range of companies.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Branding (Marketing); Private equity; Business enterprises -- Finance